1992
DOI: 10.1111/j.1365-2265.1992.tb02299.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin secretion, insulin sensitivity and hepatic insulin extraction in primary hyperparathyroidism before and after surgery

Abstract: Patients with pHPT exhibited decreased insulin sensitivity and insulin hypersecretion. The latter is only partially ameliorated by increased hepatic insulin extraction. After surgery, although the biochemical abnormalities were fully reversible, the metabolic changes improved only partially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 34 publications
6
55
0
1
Order By: Relevance
“…Present findings, in agreement with results of other Authors [6,11,32,33], have also shown that insulin resistance is significantly increased in PHPT patients without altered glucose tolerance and cardiovascular risk factors; this increased insulin resistance probably leads over many years to metabolic disorders, hypertension, and to increased cardiovascular morbidity and mortality. Noteworthy our data show a positive correlation between serum total calcium levels and insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…Present findings, in agreement with results of other Authors [6,11,32,33], have also shown that insulin resistance is significantly increased in PHPT patients without altered glucose tolerance and cardiovascular risk factors; this increased insulin resistance probably leads over many years to metabolic disorders, hypertension, and to increased cardiovascular morbidity and mortality. Noteworthy our data show a positive correlation between serum total calcium levels and insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…Hyperparathyroidism, found in vitamin D depletion, may be such a link. There is evidence that insulin resistance occurs in primary hyperparathyroidism, which improves after parathyroidectomy [10]. Impaired insulin release, insulin resistance and impaired glucose tolerance developing in subjects with renal failure improves with the administration of 1,25(OH) 2 D 3 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also evidence, that phosphate supplementation in glucose intolerant hypophosphatemic patients improves glucose tolerance significantly (Wittmann and Nagy, 1997). In addition, surgical treatment of pHPT at least partly reverses IGT and insulin resistance in these subjects (Prager et al, 1990;Kautzky-Willer et al, 1992).…”
Section: Introductionmentioning
confidence: 99%